Cartilage-targeting and dual MMP-13/pH responsive theranostic nanoprobes for osteoarthritis imaging and precision therapy. (December 2019) - Chen, Haimin; Qin, Zainen; Zhao, Jinmin; He, Yi; Ren, En; Zhu, Ye; Liu, Gang; Mao, Chuanbin; Zheng, Li
Abstract: Osteoarthritis (OA) microenvironment is marked by matrix metalloproteinases-13 (MMP-13) overexpression and weak acidity, making it possible to develop dual-stimuli responsive theranostic nanoprobes for OA diagnosis and therapy. However, current MMP/pH-responsive systems are not suitable for OA because of their poor biocompatibility, poor degradation and non-cartilage-targeting of the responsive probes. Here we designed a novel biocompatible cartilage-targeting and MMP-13/pH-responsive ferritin nanocages (CMFn) loaded with an anti-inflammatory drug (Hydroxychloroquine, HCQ), termed CMFn@HCQ, for OA imaging and therapy. We found that CMFn could be smartly "turned on" to emit light for OA imaging in response to the level of overexpressed MMP-13 in OA microenvironment, corresponding to the degree of OA severity. Thus the light intensity detected reflected the degree of OA severity, enabling the precise disease classification by our CMFn. CMFn could be "turned off" to stop emitting light in the normal joint. CMFn@HCQ nanocages could target the cartilage and release HCQ in the OA joint specifically under acidic pH conditions in a sustained manner, prolonging the drug retention time to 14 days to remarkably reduce synovial inflammation in the OA joints. The CMFn@HCQ nanocages represent a smart dual-stimuli responsive and cartilage-targeting nanoprobes, and hold promise for imaging-guided precision therapy for OA.